Knowledge Management Capabilities and Firm Performance: Evidence from Nepalese Commercial Banks - Chalise, Mahananda; Adhikari, Rama (Journal of Nepalese Business Studies, 2024)
Every corporate sector's success depends on its knowledge capabilities to produce value and take competitive advantages. The effective management of that resources by corporate is to improve the firm’s efficiency. Organizations attempt to coordinate these knowledge resources in new and distinct ways and transform them into innovative resources better than those of their competitors. The aim of this study is to investigate the role and impact of knowledge management capabilities in firm’s performance. This study was conducted on the Nepalese commercial banks. As part of the study, knowledge management was thought to comprise the key constructs of knowledge infrastructure and knowledge process capabilities. Data were collected through structured questionnaires from 384 respondents working in Nepalese commercial banks of Kathmandu valley. Descriptive statistics as well as multiple regression models have been used to analyze the data. Correlation and regression analysis have been applied to test the hypothesis. With a p-value of (0.000<0.05), it is shown that the knowledge conversion process has the highest correlation value and is positively significant when compared to all other aspects of knowledge management capacities on a firm's production. It suggests that the process of knowledge conversion and firm's performance are favorably associated. It is observed that organizational performance will be better if there is good practice of knowledge management. The results found that there is significant relationship between knowledge capabilities and firm’s performance. Managers in the banking industry may enhance decision-making, encourage innovation, enhance problem-solving skills, quicken learning and development, promote teamwork, acquire a competitive edge, and raise employee engagement through effective management of knowledge competencies.